Applying the Theory of Constraints to Improve Throughput in a Forensic DNA Laboratory. Issue 1 (7th June 2016) - Peltokorpi, Antti; Nisén, Henrik; Groop, Johan; Reinikainen, Tapani; Bengs, Auli; Pirttimaa, Markus
ABSTRACT: The Theory of Constraints (TOC) provides methods to identify and manage constraints that limit overall service performance. The study tests the applicability of the TOC method to improve forensic DNA laboratory throughput by presenting an action research study conducted in the Forensic Laboratory of the National Bureau of Investigation in Finland. Process data of samples (n = 18, 681), personnel interviews, and workshops were used as data sources to identify process constraints, to decide how to exploit the constraints, and to evaluate the success of the TOC project. Employee autonomy, although otherwise a valuable characteristic, was identified as problematic from the process flow perspective as it leads to inappropriate process metrics, lack of standardization, and impractical working hours. The solutions included: (1) more situational information about lead times and respect for time limits; (2) new options for standard statements; (3) new instructions and better technology to reduce the number of re-runs; and (4) taking into account seasonal demand in resource planning. As a result of the TOC project, average lead times decreased 45–70% (t-test, p < 0.01) in the investigated sub-processes. This article provides a practical method to utilize TOC tools to develop forensic laboratories toward their primary goals, such as quality or efficiency.